2012
DOI: 10.5194/aab-55-194-2012
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of fillet, liver and mesenteric fat in tilapia (<i>Oreochromis niloticus</i>) fed vegetable oil supplementation in the finishing period of fattening

Abstract: Tilapia (Oreochromis niloticus) previously reared on a commercial feed were shifted to 3 experimental diets with added 5 % of soybean, linseed oil or fish oils, for 42 days as a finishing diet, according to literature recommendations. Fillet, liver and mesenteric fat total lipid fatty acid composition was determined and evaluated taking health and dietary recommendations into consideration. It was found that dietary vegetable oil fatty acids are effectively incorporated into tilapia hepatic and muscular total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…The present research confirmed that the fatty acid composition of several tilapia tissues is directly influenced by the dietary lipid source as described previously (Szabó et al, 2011; Molnár et al 2012), although this is a general statement since there are some specificities in both tissues and fatty acids independent of diet. The most abundant fatty acids in diets TFO, Low‐CO and Med‐CO were 16:0, 18:1n‐9 and LOA, and this was clearly reflected in all tissues of fish fed those diets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present research confirmed that the fatty acid composition of several tilapia tissues is directly influenced by the dietary lipid source as described previously (Szabó et al, 2011; Molnár et al 2012), although this is a general statement since there are some specificities in both tissues and fatty acids independent of diet. The most abundant fatty acids in diets TFO, Low‐CO and Med‐CO were 16:0, 18:1n‐9 and LOA, and this was clearly reflected in all tissues of fish fed those diets.…”
Section: Discussionsupporting
confidence: 92%
“…The present research confirmed that the fatty acid composition of several tilapia tissues is directly influenced by the dietary lipid source as described previously (Szabó et al, 2011;Molnár et al 2012), although this is a general statement since there are some specificities in both tissues and fatty acids independent of diet.…”
Section: Discussionsupporting
confidence: 91%
“…Similar studies performed on tropical (Clement & Lovell, 1994) and temperate (Ahlgren et al, 1994) freshwater fishes showed the dominance of these fatty acids in the tissue of fish. Overall, the results of fatty acid concentration were consistent with the results reported for tilapia in tank culture system (Karapanagiotidis et al, 2006;Molnar et al, 2012;Ma et al, 2015) and in pond culture systems (Ponzoni et al, 2008;Nguyen et al, 2010). Some of the GIFT tilapia reared in pond were observed to have spawned during the experimental period (GIFT tilapia fingerlings were noticed nearby the cage during feeding time).…”
Section: Discussionsupporting
confidence: 88%
“…Croft et al, (1988) reported antagonistic effect of EPA on ARA in rats' leukocytes. The ratio of ARA to -3 PUFAs (EPA and DHA) in human diets is also an important factor (Molnar, 2012). Although the issue whether dietary ARA is harmful or not is unequivocal since ARA has both pro and antithrombotic and inflammatory effects (Netleton, 2008).…”
Section: Figmentioning
confidence: 99%